Assessing the effects of oil palm replanting on arthropod biodiversity. Issue 1 (27th September 2020) - Pashkevich, Michael D.; Aryawan, Anak Agung Ketut; Luke, Sarah H.; Dupérré, Nadine; Waters, Helen S.; Caliman, Jean‐Pierre; Naim, Mohammad; Turner, Edgar C.
Abstract: Palm oil is the most traded vegetable oil worldwide. Production is concentrated in Southeast Asia, where established oil palm plantations dominate the landscape in many regions. Although levels of biodiversity are much lower than in forest, mature oil palm plantations can support a wide range of generalist species. However, these species may be threatened, as large areas of plantation have already been, or will soon be, replanted as they near the end of their productive life (20–30 years). Replanting changes vegetation complexity and microclimate, but short‐ and long‐term effects on biodiversity are largely unstudied. We surveyed an oil palm chronosequence (first‐generation mature palms, and replanted second‐generation palms aged 1, 3 and 8 years) in an industrial plantation in Riau, Indonesia to assess the impacts of replanting over an 8‐year period on arthropods in the ground, understorey and canopy microhabitats. Replanting was carried out using current recommended strategies, which included staggering replanting events to promote landscape‐level heterogeneity, retaining mature oil palm riparian buffers, planting a cover crop immediately after replanting, and using chopped mature palms as mulch after clearance. We assessed changes in total arthropod abundance and order‐level community composition, as well as specific changes in spider communities. We observed no significant declines in total arthropod abundance after replanting, but arthropod order‐level community composition varied across the chronosequence in all microhabitats. These findings were replicated, or more pronounced, in spider‐specific analyses. Spider abundance and species richness decreased in the understorey in the first year after replanting (although these returned to pre‐replanting levels after 3 years), and spider species‐level community composition in all microhabitats differed significantly across the chronosequence. Synthesis and applications . Our findings indicate that total arthropod abundance is resilient to replanting of oil palm, but that replanting changes total arthropod and spider community composition and decreases spider abundance and species richness in some microhabitats. While it is somewhat encouraging from a management perspective that recommended replanting strategies maintain overall arthropod abundance, the changes in arthropod composition and spider biodiversity that we observed may impact ecosystem processes, such as pest control, in second‐generation oil palm plantations, with potential implications for yield. Additional studies that focus on other taxonomic groups and assess the effects of individual replanting strategies are needed before the long‐term ecological impacts of replanting on existing oil palm plantations can be fully determined. Abstract : Our findings indicate that total arthropod abundance is resilient to replanting of oil palm, but that replanting changes total arthropod and spider community composition and decreases spider abundance and species richness in some microhabitats. While it is somewhat encouraging from a management perspective that recommended replanting strategies maintain overall arthropod abundance, the changes in arthropod composition and spider biodiversity that we observed may impact ecosystem processes, such as pest control, in second‐generation oil palm plantations, with potential implications for yield. Additional studies that focus on other taxonomic groups and assess the effects of individual replanting strategies are needed before the long‐term ecological impacts of replanting on existing oil palm plantations can be fully determined. Abstrak: Kelapa sawit adalah tanaman minyak nabati yang paling banyak diperdagangkan secara global. Produksi minyak kelapa sawit terpusat di Asia Tenggara, dimana perkebunan kelapa sawit mendominasi lahan perkebunan di banyak wilayah. Walapun tingkat keragaman hayati lebih rendah dibandingkan dengan hutan, pohon kelapa sawit yang sudah dewasa dapat mendukung banyak "generalist species". Akan tetapi spesies‐spesies ini dapat pula terancam keberadaannya. Luasnya area perkebunan kelapa sawit yang telah di‐replanting, atau akan di‐replanting, ketika perkebunan sudah mencapai umur yang tidak produktif (20–30 tahun). Kegiatan replanting berdampak terhadap perubahan kompleksitas vegetasi dan iklim mikro. Namun, dampak terhadap keanekaragaman hayati belum banyak teliti, baik dalam jangka pendek maupun panjang. Kami melakukan survei terhadap "chronosequence" kelapa sawit (generasi pertama, dan replanting generasi kedua, pada umur satu, tiga dan 8 tahun) di industri perkebunan kelapa sawit, Riau, Indonesia. Penelitian ini bertujuan untuk mengetahui pengaruh kegiatan replanting selama periode 8 tahun terhadap anthropoda di permukaan tanah, di bawah naungan tanaman kelapa sawit, dan di mikro‐habitat kanopi. Kegiatan replanting dilakukan sesuai dengan rekomendasi standar praktis, dimana kegiatan ini dilakukan secara luas untuk menjaga tingkat keberagaman lahan, mempertahankan (tidak ditumbang) pohon sawit dewasa di daerah aliran sungai, menanam cover crop dengan segera setelah penumbangan (sebelum penanaman) and menggunakan batang kelapa sawit yang sudah dipotong‐potong (chipping) sebagai mulsa. Kami meneliti perubahan‐perubahan yang terjadi terhadap kelimpahan arthropoda dan komposisi komunitas di tingkat ordo, dan juga perubahan yang spesifik dalam komunitas laba‐laba. Hasil pengamatan menunjukkan bahwa kegiatan replanting tidak signifikan dalam menurunkan total kelimpahan arthropoda, akan tetapi komposisi komunitas tingkat ordo berbeda selama "chronosequence" di semua habitat mikro. Hasil ini ditemukan secara berulang, atau lebih menonjol di pengamatan spesifik laba‐laba. Kelimpahan laba‐laba dan kekayaan spesies menurun di bawah naungan tanaman kelapa sawit pada tahun pertama setelah replanting (meskipun ini kembali ke level pra‐penanaman kembali setelah 3 tahun), dan komposisi komunitas di tingkat spesies laba‐laba berbeda nyata di semua habitat mikro sepanjang "chronosequence". Kesimpulan . Hasil penelitian ini menunjukkan bahwa total kelimpahan arthropoda mampu bertahan terhadap dampak kegiatan replanting di perkebunan kelapa sawit, namun kegiatan tersebut mempengaruhi komposisi komunitas total dari arthropoda dan laba‐laba, mengurangi kelimpahan laba‐laba dan kekayaan spesies pada beberapa habitat mikro. Selain terlihat menguntungkan dari perspektif manajemen, dimana standar praktis ini mampu menjaga kelimpahan arthropoda secara keseluruhan. Perubahan dalam komposisi dan biodiversitas laba‐laba yang kami teliti mungkin berpengaruh terhadap proses‐ proses dalam ekosistem, seperti pengendalian hama, potensi dalam peningkatan produksi di perkebun kelapa sawit generasi kedua. Sebelum ditentukan secara pasti terkait dampak ekologi jangka panjang dari kegiatan replanting di perkebunan kelapa sawit, diperlukan penelitian lanjutan terhadap grup taxonomy yang lain serta pengaruh strategi replanting lainnya.